Applying Six Sigma (SS) to Improve the Quality of Academic Life (QAL) - Abbas Bahia, Taher Hameed; Afrah Raheem Idan, Hinwa Hussein Ahmed (Opción, 2019)
The current study looks forward to the possible application ofSix Sigma as an input to improve the quality of academic life using aset of statistical methods through the SPSS vr.24 software. As a result,an increase in the value of (SS) by one unit leads to an increase in thevalue of (QAL) by (0.65). In conclusion, the paper shows that the lackof improvement towards the satisfaction of staff and students and thequality of its outputs and limited adoption of information technologywill lead to creativity and innovation in the field of work.